Love your body - Sanders, Jessica (Social worker) (Frances Lincoln Children's Books, 2020)
Simple text and colorful illustrations celebrate female bodies of all kinds. Encourages young female readers to love themselves and their bodies, and introduces them to things they can do to improve self-esteem and body image.